SYMMETRY OF THE BALLISTIC EQUATIONS - Malloki, Inaam A (Al-Nahrain Journal of Science, 2010)
In this paper, we characterize the possible symmetry groups of the ballistic equations, in timevariable and two spatial variables.Lie’s method of continuous transformation groups is applied and it is shown that,three-parameter Lie group of transformation acting on (t, x, y)-space is admitted by the equations